UK multi-centre retrospective study of the learning curve and relative performance of the rhythmia high density mapping system for atrial ablation. (19th May 2022) - Bates, A; Naseer, MZ; Taylor, M; Denham, N; Yue, A; Das, M; Morris, GM; Ullah, W
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): University Hospital Southampton Background: Rhythmia HDx® is a novel ultra-high density electroanatomical mapping system using an innovative 64 electrode basket catheter. A learning curve is a recognised phenomenon for any new technology and was examined in this study. Purpose: Comparison of performance, long-term success, and complications using Rhythmia for atrial ablation in the UK. Methods: Retrospective data collection from three centres across the UK from the introduction of Rhythmia. Patients were matched with controls who had undergone ablation using the well-established Carto3 mapping system. Assessed were: fluoroscopy, radiofrequency ablation and procedure times; acute and long term success, and complications. Results: 253 study patients with 253 controls were included. Significant correlations existed between procedural efficiency metrics and centre experience for de novo atrial fibrillation (AF) ablation (procedure time, Spearman's ρ = -0.624; ablation time, ρ = -0.795), and de novo atrial flutter (AFlut) ablation (ablation time, ρ = -0.566; fluoroscopy time, ρ = -0.520). No such correlations existed for redo AF, redo AFlut, de novo atrial tachycardia (AT), or redo AT cases. For de novo AF and AFlut, procedural efficiency metrics were significantly improved after 10 procedures in each centre, (procedure time [AF only, p = 0.001], ablation time [AF, p < 0.0005; AFlut p < 0.0005] and fluoroscopy time [AFlut only, p = 0.0022]), and became comparable to controls (Figures 1 and 2). Acute success and long-term success did not see significant improvement with experience but were comparable to the control group. There was no relationship between experience and complications, which were comparable to Carto3 (3.6% in both groups). Conclusion: A short learning curve exists with the use of Rhythmia HDx for standardised procedures (de novo AF / AFlut). Procedural performance improves and becomes comparable to Carto3 following 10 cases at each centre. Clinical outcomes at 6 and 12 months, and complications are not affected by this learning curve and remain comparable with controls.